The agenda setting on facebook: Plebiscite campaign for peace in Colombia [La agenda setting en la red social Facebook: Campaña del plebiscito por la paz en Colombia] (2018)
This study examines the relation between the entities that set the agenda during the plebiscite campaign for peace in Colombia and the topic promoted on their official Facebook pages. In addition, it was analyzed whether the social interaction was influenced by the issue promoted in the official pages as well as by the entity that set the agenda. The quantitative method was used and a sample from 58 posts, published by El Tiempo and El Colombiano newspapers, the Office of the High Commissioner for Peace and the Centro Democratico political party, was taken. In conclusion, it was found that there was a statistically significant relationhip between the entity that sets the agenda and the variables on the agenda referring to peace agreements, the end of the conflict, and the implementiation, verification and validation, which confirmed H1 of this study. Regarding H2 and H3, this study found that social interaction based on actions using like and share was not influenced by the topic of the agenda, but it was influenced by the entity setting it. In conclusion, the study shows that social networks are enabling counter-hegemonic and/or minority groups agendabuilding, configuring in this way a more diverse plural, and contradictory mediated public sphere. © 2018 Universidad de Caldas. All rights reserved.